PERAKITAN SISTEM PENDINGIN ENGINE MOTOR GRADER TIPE 4BT3.9-C110 - , WIDODO PINARCAHYA PUTRA; , Radhian Krisnaputra, ST. M. Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Motor grader is one of the tool in the mining industry, forestry or construction. Motor grader operation time is very long therefore spend long time to achieve maximum performance need to keep the engine temperature and long service life while a proper cooling is needed. If the cooling flow stops, it can create severe damages to the engine, example it cause shrinking curve cylinder bore and cylinder head but when it is too cold can reduce machine performance when the machine while use to work. Therefore need to be equipped engine cooling system in order to keep the engine operating temperature. Cooling method used on motor grader is water cooling systems. The method used in this thesis is consist of several steps. First do a literature study. Second observations. Third interviewed. Fourth designing proper cooling system for the engine. From the results of the cooling system assembly can be concluded that the assembly of the cooling system is to function properly, the power of determining the use of the radiator, fan, inlet and exit as well as additional components.